“HIMMATI” as a Modification of Base Learning to Identify Al-Qur’an - Istiqomah, Himatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This research aims to dewascribe a book about modification base learning to identify Al-Qur’an, Himmati . What is it? and How is it? This belongs to library research with qualitative descriptive analysis. The result shows that: Himmati is the series book about a Modification of Base Learning to Identify Al-Qur’an. It consists of five volumes with seven series. The 1 st is to identify the letters. It consists of three letters with three vowels that arranges the words in Al-Qur’an. The 2 nd (2A and 2B) is to identify the words. It consists of completion words from the letters arrangement in the 1 st volume and additional words with wazan similarity in Al-Qur’an. The 3 rd (3A and 3B) is to identify Tajwid. It consists of the phrases and the sentences in Al-Qur’an. The 4 th is to identify Gharib. It consists of foreign words and rules of exclusion in Al-Qur’an. The last (the 5 th ) is to identify the waqof signs in the verses of Al-Qur’an, especially the verses about attitude and morals. The classification and structuring above aims to introduce Al-Qur’an to own learners from the simplest part to the most complex. Besides that, each of the series are made colorful according to the frequency gradations. So, they will enjoy learning and will not feel bored.